Dinâmica de nitrogênio no contínuo solo-planta em área alterada e cultivada com à fertilização mineral - Pereira, Luis Octávio Vieira (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
According to recent estimates, one-fifth of Legal Amazon forest cover has been intensely altered, and although deforestation rates fluctuate, they have remained growing and consequently have promoted forest degradation. Species of the Fabaceae family have been indicated for the recovery of altered areas due to functional characteristics such as rusticity, biological nitrogen fixation, fast growing and great biomass production. An important fact is that only some of these species are able to fix atmospheric nitrogen, a feature that deserves attention given that in degraded tropical areas this element can become a limiting factor to plant establishment and growth. In this sense, we studied the interspecific differences in the mineral nitrogen partitioning, assimilation and allocation in six Fabaceae species cultivated on a degraded area where soil nutrient availability was increased by fertilizer application. In addition, intraspecific differences in nitrate and ammonium partitioning, assimilation and allocation were evaluated in A. mangium and D. odorata species cultivated with and without fertilization. The experiment was installed in an area around the Balbina Hydroelectric Power Plant (HPP - Balbina) in the municipality of Presidente Figueiredo, AM. Of all six evaluated species, three are able to perform biological nitrogen fixation (A. mangium, C. fairchildiana and I. edulis) while the other half (S. reticulata, D. odorata and C. tocantinum) are not. The variables analyzed were soil, root, leaf and sap NH 4 +, and NO 3 – contents; root and leaf nitrate reductase activity; nitrogen use efficiency, nodule production amount of leaf chloroplastidic pigments and soluble proteins. The strategies of partitioning and assimilation of mineral nitrogen varied specifically without grouping by functional traits. Protein content was higher in all noduliferous species. Nitrogen efficiency was correlated with photosynthetic capacity, but not with total leaf nitrogen content. C. fairchildiana species showed lower nodule production than the other noduliferous species. A. mangium cultivated with and without fertilizer application exhibited similar strategy of partitioning and assimilation of nitrate, although fertilization stimulated nodule production. D. odorata changed its nitrate assimilation strategy when fertilized and accumulated more nitrate in roots and leaves when it was not fertilized.
Keywords: Fabaceae arbóreas; Compostos nitrogenados; Recuperação da floresta